Taxonomic and functional biogeographies of soil bacterial communities across the Tibet plateau are better explained by abiotic conditions than distance and plant community composition - Qingqing Liang; Heidi K. Mod; Shuaiwei Luo; Beibei Ma; Kena Yang; Beibei Chen; Wei Qi; Zhigang Zhao; Guozhen Du; Antoine Guisan; Xiaojun Ma; Xavier Le Roux (Molecular Ecology, 2023)
The processes governing soil bacteria biogeography are still not fully understood. It remains unknown how the importance of environmental filtering and dispersal differs between bacterial taxonomic and functional biogeography, and whether their importance is scale‐dependent. We sampled soils across the Tibet plateau, with distances among plots ranging from 20 m to 1550 km. Taxonomic composition of bacterial community was characterized by 16S amplicon sequencing and functional community composition by qPCR targeting 9 functional groups involved in N dynamics. Factors representing climate, soil and plant community were measured to assess different facets of environmental dissimilarity. Both bacterial taxonomic and functional dissimilarities were more related to abiotic dissimilarity than biotic (vegetation) dissimilarity or distance. Taxonomic dissimilarity was mostly explained by differences in soil pH and mean annual temperature (MAT), while functional dissimilarity was linked to differences in soil N and P availabilities and N:P ratio. Soil pH and MAT remained the main determinants of taxonomic dissimilarity across spatial scales. In contrast, the explanatory variables of N‐related functional dissimilarity varied across the scales, with soil moisture and organic matter having the highest role across short distances ( ~660 km). Our results demonstrate how biodiversity dimension (taxonomic versus functional aspects) and spatial scale influence the factors driving soil bacterial biogeography.

The relationships of plant species occupancy to niches and traits vary with spatial scale - Heidi K. Mod; Tuuli Rissanen; Pekka Niittynen; Janne Soininen; Miska Luoto (Journal of Biogeography, 2023)
Aim Support for different underlying mechanisms of species occupancy is inconsistent, yet this could be related to spatial scale. Since abiotic filtering typically acts at broader scales than biotic interactions, we hypothesise that occupancy could be more driven by species' abiotic niche (i.e. tolerance and preference of abiotic conditions) at broad scales, whereas species' traits affecting competitive ability could be more important at fine scales. Here, we test these hypotheses by assessing relationships of occupancy to niche and trait metrics across spatial scales. Location Four study areas located north of Arctic Circle. Taxon Vascular plants. Methods We derived occupancy for 106 species at four spatial scales (micro‐scale with plot size of 0.04 m 2 and extent of 2 km, local‐scale with plot size of 4 m 2 and extent of 40 km, regional‐scale with plot size of 4 ha and extent of 800 km, and polar‐scale with plot size of 4 km 2 and extent of 5200 km). We then assessed using generalized additive models whether the relationships between occupancy and species' niche breadth, niche marginality, intraspecific trait variability (ITV) and trait distinctiveness vary across the scales. Results At the finer scales, ITV (especially of specific leaf area) had the highest contribution with positive relationship in explaining occupancy. At the broader scales, occupancy was better explained by niche metrics. Especially at the broadest scale, the occupancy had a positive relationship with species' climatic tolerance. Main Conclusions Abiotic filtering, especially related to macro‐climate, drives species occupancy at broader spatial scales while biotic interactions are relatively more important at local scales. This scale‐dependency of factors behind species occupancy should be accounted for when, for example, planning conservation of rare species, forecasting invasions or anticipating the effects of changing climate on biota at local versus global scales.

Soil protist function varies with elevation in the Swiss Alps - Florent Mazel; Lucie Malard; Hélène Niculita‐Hirzel; Erika Yashiro; Heidi K. Mod; Edward A. D. Mitchell; David Singer; Aline Buri; Eric Pinto; Nicolas Guex; Enrique Lara; Antoine Guisan (Environmental Microbiology, 2022)
Summary Protists are abundant and play key trophic functions in soil. Documenting how their trophic contributions vary across large environmental gradients is essential to understand and predict how biogeochemical cycles will be impacted by global changes. Here, using amplicon sequencing of environmental DNA in open habitat soil from 161 locations spanning 2600 m of elevation in the Swiss Alps (from 400 to 3000 m), we found that, over the whole study area, soils are dominated by consumers, followed by parasites and phototrophs. In contrast, the proportion of these groups in local communities shows large variations in relation to elevation. While there is, on average, three times more consumers than parasites at low elevation (400–1000 m), this ratio increases to 12 at high elevation (2000–3000 m). This suggests that the decrease in protist host biomass and diversity toward mountains tops impact protist functional composition. Furthermore, the taxonomic composition of protists that infect animals was related to elevation while that of protists that infect plants or of protist consumers was related to soil pH. This study provides a first step to document and understand how soil protist functions vary along the elevational gradient.

Greater topoclimatic control of above‐ versus below‐ground communities - Heidi K. Mod; Daniel Scherrer; Valeria Di Cola; Olivier Broennimann; Quentin Blandenier; Frank T. Breiner; Aline Buri; Jérôme Goudet; Nicolas Guex; Enrique Lara; Edward A. D. Mitchell; Hélène Niculita‐Hirzel; et al. (Global Change Biology, 2020)
Assessing the degree to which climate explains the spatial distributions of different taxonomic and functional groups is essential for anticipating the effects of climate change on ecosystems. Most effort so far has focused on above‐ground organisms, which offer only a partial view on the response of biodiversity to environmental gradients. Here including both above‐ and below‐ground organisms, we quantified the degree of topoclimatic control on the occurrence patterns of >1,500 taxa and phylotypes along a c. 3,000 m elevation gradient, by fitting species distribution models. Higher model performances for animals and plants than for soil microbes (fungi, bacteria and protists) suggest that the direct influence of topoclimate is stronger on above‐ground species than on below‐ground microorganisms. Accordingly, direct climate change effects are predicted to be stronger for above‐ground than for below‐ground taxa, whereas factors expressing local soil microclimate and geochemistry are likely more important to explain and forecast the occurrence patterns of soil microbiota. Detailed mapping and future scenarios of soil microclimate and microhabitats, together with comparative studies of interacting and ecologically dependent above‐ and below‐ground biota, are thus needed to understand and realistically forecast the future distribution of ecosystems.

Scaling the linkage between environmental niches and functional traits for improved spatial predictions of biological communities - Antoine Guisan; Heidi K. Mod; Daniel Scherrer; Tamara Münkemüller; Julien Pottier; Jake M. Alexander; Manuela D'Amen (Global Ecology and Biogeography, 2019)
Issue Approaches to predicting species assemblages through stacking individual niche‐based species distribution models (S‐SDMs) need to account for community processes other than abiotic filtering. Such constraints have been introduced by implementing ecological assembly rules (EARs) into S‐SDMs, and can be based on patterns of functional traits in communities. Despite being logically valid, this approach has led to a limited improvement in prediction, possibly because of mismatches between the scales of measurement of niche and trait data. Evidence S‐SDM studies have often related single values of a species’ traits to environmental niches that are captured by abiotic conditions measured at a much finer spatial scale, without accounting for intraspecific trait variation along environmental gradients. Many pieces of evidence show that omitting intraspecific trait variation can hinder the proper inference of EARs from trait patterns, and we further argue that it can therefore also affect our capacity to spatially predict functional properties of communities. In addition, estimates of environmental niches and trait envelopes may vary depending on the scale at which environmental and trait measurements are made. Conclusion We suggest that to overcome these limitations, surveys sampling both niche and trait measurements should be conducted at fine scales along wide environmental gradients, and integrated at the same scale to test and improve a new generation of spatial community models and their functional properties.

Impact of biotic interactions on biodiversity varies across a landscape - Heidi K. Mod; Risto K. Heikkinen; Peter C. le Roux; Mary S. Wisz; Miska Luoto (Journal of Biogeography, 2016)
Aim Biotic interactions have a central role in defining species assemblages, realized both through negative and positive impacts. However, forecasts of how these interactions affect biodiversity across landscapes are challenging (and lacking) because the outcome of interactions depends not only on the identity of the interacting species but also on local environmental conditions. Thus, we study how biotic interactions manifest across a landscape. Location High‐latitude northern Finland and Norway (69° N, 21° E). Methods We modelled the influence of a dominant shrub, Empetrum hermaphroditum , on spatial patterns of species richness of vascular plants, bryophytes and lichens (using cover of the shrub as a proxy for the frequency and intensity of interaction with other species) across a topographically variable landscape. Results The relationship between the cover of the dominant shrub and species richness differed between guilds, being strongest for vascular plant richness, and varied considerably along environmental gradients. The dominant shrub showed stronger negative impact on vascular plant richness under less abiotically extreme conditions. For lichens, the relationship was the opposite: under mild conditions, species richness increased with the cover of the shrub. Incorporating specific leaf area ( SLA ) data into analyses revealed that the dominant shrub affected species with high SLA (typically competitive species of resource‐rich environments) most negatively. Main conclusions Our findings show how the impact of a dominant species varies across a landscape, with distinctly different effects on competitive and stress‐tolerant vascular plants, and on bryophytes and lichens. Spatial predictions of biodiversity trends under global environmental change could, therefore, critically benefit from accounting for context‐dependent impacts of biotic interactions.

Contrasting effects of biotic interactions on richness and distribution of vascular plants, bryophytes and lichens in an arctic–alpine landscape - Heidi K. Mod; Risto K. Heikkinen; Peter C. le Roux; Henry Väre; Miska Luoto (Polar Biology, 2016)